Optical characteristics of the undamaged and laser damaged K9 glass in terahertz band - Xiaoyan Shang; Wei Shi; Wenwen Hai; Junhong Su; Chengang Dong (Materials Research Express, 2020)
K9 glass is an important optical element of the high energy laser system. In an attempt to investigate the variation of optical properties of K9 glass before and after laser induced damage, based on the transmission terahertz time-domain spectral system, the undamaged and the damaged K9 glasses induced by laser were tested to obtain the terahertz time-domain and frequency-domain spectra and the refractive index and absorption coefficient of the samples were calculated in terahertz band for further analysis. Results show that with the increase of laser energy, from the undamaged to the damaged K9 glasses to different extent, the peak to peak value in time domain and the amplitude value in frequency domain present a decreasing trend in varying degrees, and in the 0.4 ∼ 0.5 THz band, the absorption coefficient increases continuously with a slight change of refractive index, which indicates that K9 glass not only appears the melting and fracture in the macroscopic morphology after laser-induced damage, but also forms non-bridged oxygen atoms in its microstructure with more ion bonds and free electrons and the change of ion polarization. In this regard, this paper provides a technical basis for exploring the micro characteristics of K9 glass after laser-induced damage, and lays a good foundation for the application of terahertz time-domain spectroscopy to laser-induced damage analysis.